Предмет: Математика,
автор: Аноним
36a²-(a²+9)²
разложите на множители пожалуйста
Ответы
Автор ответа:
0
по формуле:
a²-b²=(a-b)(a+b)
получаем:
![(6a-(a^2+9))(6a+(a^2+9))=(6a-a^2-9)(6a+a^2+9) (6a-(a^2+9))(6a+(a^2+9))=(6a-a^2-9)(6a+a^2+9)](https://tex.z-dn.net/?f=%286a-%28a%5E2%2B9%29%29%286a%2B%28a%5E2%2B9%29%29%3D%286a-a%5E2-9%29%286a%2Ba%5E2%2B9%29)
![-(a^2-6a+9)(a^2+6a+9)=-(a-3)^2(a+3)^2 -(a^2-6a+9)(a^2+6a+9)=-(a-3)^2(a+3)^2](https://tex.z-dn.net/?f=-%28a%5E2-6a%2B9%29%28a%5E2%2B6a%2B9%29%3D-%28a-3%29%5E2%28a%2B3%29%5E2)
a²-b²=(a-b)(a+b)
получаем:
Похожие вопросы
Предмет: Русский язык,
автор: emirzoldosbekov048
Предмет: Математика,
автор: Аноним
Предмет: Математика,
автор: Аноним
Предмет: Физика,
автор: hidanchik24
Предмет: Химия,
автор: с45